Silence and the Regulation of Feminist Anger in Young Adult Rape Fiction. Issue 2 (1st July 2019) - Altrows, Aiyana
Abstract : Bringing rape stories into popular discussion was a crucial success of the Second Wave Women's Liberation movement. Popular culture is now inundated with rape stories. However, the repetitive scripts and schemas that dominate these are often informed by neoliberal individualism that is antithetical to feminism. The contradictions that characterize the tensions between feminism and neoliberalism in these texts are typically postfeminist, combining often inconsistent feminist rhetoric with neoliberal ideology. By examining the use of the silent victim script in young adult rape fiction, in this article I argue that most young adult rape fiction presents rape as an individual, pathological defect and a precondition to be managed by girls on an individual basis, rather than an act of violence committed against them.